Length–weight relationships of eight Asian freshwater fish species in Nam Theun 2 Reservoir (Laos PDR). (29th March 2017) - Tessier, A.; Guillard, J.; Chanudet, V.; Cottet, M.
Summary: Length–weight relationships (LWRs) were determined for eight Asian freshwater fish species that were not yet recorded in any peer‐reviewed journal indexed in the Web of Science or the FishBase database. Fish specimens from Nam Theun 2 reservoir in Lao PDR, were collected from April 2012 to August 2016 using several methods to cover a large size‐spectrum for each species. For LWRs using the general equation from Beckman (1948), the parameter b (slope value on the growth pattern) ranges from 2.908 ( Puntius brevis ) to 3.429 ( Rasbora paviana ). This study provides an update in maximum lengths for two species and first LWRs for eight common freshwater species found mainly in reservoirs, and thus represents a means for further population dynamic evolution analyses and local fisheries management.